Efeitos farmacológicos do disseleneto de difenila em modelos de toxicidade induzida por organofosforados em ratos - Acker, Carmine Inês (2012)
Pesticides are substances used in agricultural areas and public health programs to control pests and disease vectors. Among pesticides, organophosphates (OPs) are considered the most toxic to vertebrates. Diphenyl diselenide [(PhSe)2] is an organoselenium compound that presents pharmacological activities, among that the antioxidant effect. Therefore, the aim of this study was to evaluate the pharmacological effects of (PhSe)2 in acute models of toxicity induced by chlorpyrifos (CPF) and acephate (AC) in rats, as well as to investigate the hyperglycemic and hyperlipidemic effects of CPF which has not been described. In the first experimental protocol (article 1), the effect of (PhSe)2 on hepatic and hematological toxicity induced by CPF in rats was evaluated. The animals were pre-treated by intragastric route (p.o.) with (PhSe)2 (5 mg/kg) once a day for 7 days. On the 8th and 9th days, (PhSe)2 (5 mg/kg; p.o.) was administered to rats 30 min prior to subcutaneous (s.c.) injection of CPF (50 mg/kg). Twenty-four hours after the last CPF injection, rats were killed. The aspartate aminotransferase (AST), alanine aminotransferase (ALT) and lactate dehydrogenase (LDH) activities were determined in plasma of rats. Lipid peroxidation, protein carbonyl and non-protein thiol (NPSH) levels as well as catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione reductase (GR) and gluthatione S-transferase (GST) activities were determined in livers of rats. Hematologic parameters were also assayed. CPF caused an increase in AST, ALT and LDH activities, an increase in lipid peroxidation and protein carbonyl levels, a decrease in NPSH levels and an inhibition of CAT, GPx, SOD and GST activities. In addition, CPF exposure caused hematologic toxicity, evidenced mainly by a decrease in total leukocytes levels. (PhSe)2 protected against toxic effects induced by CPF in rats. Moreover, (PhSe)2 increased per se NPSH levels and GST activity in livers of rats. In the second experimental protocol (article 2), the effect of (PhSe)2 on metabolic disorders induced by AC in rats was investigated. (PhSe)2 (10 or 30 mg/kg; p.o.) was administered to rats 1 hour prior to AC administration (140 mg/kg; p.o.). Two hours after AC administration, rats were killed. Glucose and corticosterone levels as well as the lipid status were determined in plasma of rats. Cardiovascular risk factor and the atherogenic index were calculated. Glycogen levels as well as tyrosine aminotransferase (TAT) and glucose-6-phosphatase (G6Pase) activities were determined in livers of rats. Cerebral acetylcholinesterase (AChE) activity was assayed. AC induced an increase in glucose, corticosterone and triglycerides (TG) levels, an increase in TAT and G6Pase activities and an inhibition of AChE activity. The cardiovascular risk factor [(TG/ high density lipoprotein (HDL)] was increased in AC exposed rats. (PhSe)2 attenuated these alterations, except for the increase of corticosterone levels and AChE activity inhibition. In the third experimental protocol (article 3), the hyperglycemic and hyperlipidemic effects of CPF in rats were investigated. The mechanisms involved in hyperglycemia induced by CPF were also studied. CPF was administered once to rats at the dose of 50 mg/kg, s.c. Animals were killed at 2, 4, 8, 12 e 24 hours after CPF administration. Glucose and corticosterone levels as well as lipid status and paraoxonase-1 (PON-1) activity were determined in plasma of rats. Cardiovascular risk factors and the atherogenic index were calculated. Glycogen levels as well as TAT and G6Pase activities were determined in livers of rats. Cerebral AChE activity was assayed. CPF caused an increase in glucose, glycogen, corticosterone, TG and low density lipoprotein (LDL) levels, an increase in TAT and G6Pase activities, a decrease in HDL levels and PON-1 activity and AChE activity inhibition. The cardiovascular risk factors and atherogenic index were increased in CPF exposed rats. The results of the present study demonstrated that (PhSe)2 protected against toxic effects induced by CPF and AC in rats. CPF exposure caused hyperglycemia and hyperlipidemia in rats. The gluconeogenesis pathway activation is involved in the hyperglycemic effect caused by CPF. Considering that the crescent use of OPs worldwide has been the cause of many severe human poisoning cases, the results of the present work are of great importance, since that (PhSe)2 may represent an alternative to alleviate the OPs-induced toxicity.